CONTROL DE EXISTENCIA Y OPTIMIZACIÓN DE INVENTARIOS DEL ALMACÉN BODEGA DE LA UTB - ALVAREZ GARCIA, ELVIS FERNANDO (2018)
All institutions of an educational nature at any of their levels must consider important to maintain control over the supplies purchased for development in each One of its activities, whether administrative or educational, for research purposes was chosen the warehouse warehouse of the Technical University of Babahoyo to carry out a study and so on prescribe the problem that it maintains. The present research work focuses on stock control and optimization inventory of the warehouse warehouse of the Technical University of Babahoyo, lack a exact control, being this the fundamental item of the institution that in conjunction with the controls Inmates will allow decision making to protect and safeguard assets, verify the accuracy and reliability of the accounting data. It considered sources and knowledge necessary to carry out this research through bibliographic compilation of books and internet, being the main objective of this case study determine the absence of organization in stock control and its impact on the inventory optimization of the warehouse warehouse of the Technical University of Babahoyo, besides knowing the controls of income and outputs of supplies, as well as the supply system for distribution in the different departments of the institution, identifying the advantages and disadvantages that it currently possesses, in addition to the which causes the absence of controls on stock levels. The methodology to be used is descriptive in order to analyze the facts seeking to specify the characteristics of the institution to be investigated, in addition to the modality field and documentary so interviews were conducted based on questionnaires that they allowed gathering the necessary truthful and reliable information. 2 This research will be carried out with the purpose of generating knowledge about the perfect the monitoring of the stocks in the warehouse, this will be achieved by implementing adequate internal controls to safeguard and preserve stocks within the institution